Fall fertilization of Holm oak affects N and P dynamics, root growth potential, and post-planting phenology and growth - Oliet, Juan a; Salazar, José M.; Villar, Rafael; Robredo, Eduardo; Valladares, Fernando (Annals of Forest Science, 2011)
& Introduction For Holm oak (Quercus ilex L.), a flush growing species, nutrient loading during the growing season is difficult and can lead to a low nutrient status of the seedlings. To provide insights about Holm oak nutrient dynamics during fall in the nursery and subsequent planting performance, a factorial nursery experiment was conducted in a mild fall–winter area testing the effects of timing of fertilization (early and late fall) and rate (two doses of a NPK fertilizer that applied 28 and 56 mg N per seedling), followed by an experimental plantation. & Results Biomass, allocation pattern, shoot N and K, and root K were unaffected by both rate and timing of fall fertilization. However, shoot P concentration of fall fertilized plants was significantly increased, and root P concentration was enhanced by applying fertilizer at either the highest rate or during early fall. This revealed a different nutrient dynamics during fall that was dependent on the specific nutrient and plant component. & Discussion Root growth potential was positively correlated to nursery root P concentration. Six months after planting, fall fertilized plants showed higher shoot biomass, higher proportion of new leaves, and faster development, producing leaves earlier compared with unfertilized plants. & Conclusion It is concluded that early fall fertilization promotes nutrient loading of P in Holm oak, with significant effects on root growth potential and field growth by means of a phenologically earlier development and a higher aboveground biomass
Keywords: late season fertilization; Nutrient loading; phosphorus; Quercus ilex; root growth potential